Sportlight on graduate student: Nurulhusna Ab. Hamid - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
Nurulhusna Ab. Hamid, 28 years old, is a native of Langgar, Alor Star, Kedah. She received her eai1y education in Alor Star and then pursued bachelors and masters degrees at Universiti Malaysia Sabah in Biotechnology. After a career stint with FA Herbs Sdn. Bhd. as QNQC scientist, Nurulhusna assumed her present post as Research Officer at the Institute for Medical Research (IMR), Kuala Lumpur. She is assigned to the Medical Entomology Unit.